Concha bullosa surgery and the distribution of human olfactory neuroepithelium - Apuhan, Tayfun; Yıldırım, Yavuz Selim; Şimsek, Tuğçe; Yılmaz, Fahrettin; Yılmaz, Fahri (Springer, 2013)
In bullous middle turbinate surgery, controversy exists over which side of the bullous middle turbinate should be removed, as the distribution of human olfactory neuroepithelium is unclear. This study evaluated whether the middle turbinate tissue of patients undergoing endoscopic concha bullosa surgery contains functional olfactory epithelium. This prospective clinical study was conducted in tertiary referable center. It detected 70 conchae bullosa in 48 patients with sinonasal symptoms, who underwent paranasal computed tomography (CT) that showed pneumatization of the middle concha. All samples were obtained under general anesthesia. Three samples were obtained from each bullous middle turbinate: one each from the anterior, medial, and lateral portions. The mucosa from each sample was stained with olfactory marker protein (OMP). In total, 210 middle turbinate samples were taken from 48 patients during endoscopic surgery for conchae bullosa. The patients were 22 females and 26 males. Of the 70 conchae bullosa, OMP-stained nerve tissue was found in the lateral, anterior and medial aspects of 57 (81.4 %), 42 (60.0 %) and 23 (32.8 %) of the bullous middle turbinates, respectively. OMP-stained nerve tissue was found in 122 (58.1 %) of the 210 bullous middle turbinate tissue samples. OMP-stained nerve tissue was found on the lateral surface of the bullous middle turbinate more often than the medial surface. Therefore, during the concha bullosa surgery, OMP-stained nerve tissue found at least in the medial part of concha, suggested that the opening of the medial part of middle concha.
WOS: 000315443000023
PubMed ID: 22941439
Keywords: Concha Bullosa Surgery; Olfactory Neuroepithelium; Olfactory Mucosa; Concha Bullosa; Middle Turbinate; OMP; Endoscopic surgery